Prevalence of depression in patients with type 2 diabetes mellitus and its association with fasting blood sugar levels, in an urban area of Kancheepuram district, Tamil Nadu - V. M, Anantha Eashwar; S., Gopalakrishnan; R., Umadevi (International Journal Of Community Medicine And Public Health, 2017)
Background: Type 2 diabetes mellitus (T2DM) and depressive disorders are among the major health problems in our community. Chronic medical conditions, like diabetes are affectively stressful for patients and may influence pathophysiologic mechanisms as well as mood. This can lead to depression and poor prognosis of T2DM. This study was done to assess the prevalence of depression among T2DM patients and its association with glycemic control. Methods: This descriptive cross sectional study was carried out among 300 T2DM patients attending Urban Health Training Center (UHTC), Anakaputhur, which belongs to the urban field practice area of our institution. Fasting Blood Sugar levels (FBS) were assessed retrospectively from their medical records; and they were screened for depression by administering the nine items, “Patient Health Questionnaire - 9”. Results: Of the 300 T2DM patients, 54% were females. The mean age of the participants was 53±9.7 years. 31% of the study participants had fasting blood sugar (FBS) levels above 125 mg/dl. Depression was present in 39.7% of the individuals, among which, 17.3% had mild depression, 13% had moderate depression, 6.7% had moderately severe depression and 2.7% had severe depression. Depression was found to be significantly associated with increasing fasting blood sugar levels, diabetic complications, female gender and diabetic treatment. Conclusions: This study shows that depression is highly prevalent among T2DM patients and is associated with poor prognosis, as reflected by poor glycemic control (FBS) and the occurrence of diabetic complications. So screening and counselling for depression among T2DM patients have to be carried out for optimum control and treatment of T2DM.